GENOSIDA DALAM PERSPEKTIF HUKUM INTERNASIONAL: PENGERTIAN, DAN YURISDIKSI - Kilikily, Yusuf Hofni Junior (Jurnal Ilmu Hukum Sui Generis, 2025)
The objectives of this research are (1) to define genocide and (2) to examine the jurisdiction of international law over the crime of genocide. This study employs a normative legal research method with statutory and conceptual approaches. The findings indicate that (1) genocide is any act committed with the intent to destroy, in whole or in part, a national, ethnical, racial, or religious group, as defined in the 1948 Genocide Convention, emphasizing the element of 'intent' to annihilate such a group. (2) The International Criminal Court possesses jurisdiction over perpetrators of genocide under Article 5 of the Rome Statute, and this research further explores the evolution of jurisdiction concerning the crime of genocide.